“DIDATICS”, GAMES, SCOUTS, PHYSICAL, PSYCHOLOGICAL AND MORAL FORMATION OF A CHILD (Fiep Bulletin - online, 2015)
The Physical Education Magazine (PEM), during 1932 and 1942, directed part of its publications to Pedagogy, what has made objectively possible to notice and discuss the influence of Pedagogy in the PEM, aiming at helping the insertion of Physical Education in the school area. The initiative is justified by scientific contribution that makes possible the understanding of pedagogical fundaments in the constitutions of Physical Education theories. The study was delimitated to the qualitative method, using the documental research. The survey made by PEM, showed how the presence of pedagogical aspects in physical activity is evident, specially directed to scouts, wanting the physical, pedagogical and moral formation of a child, this way, confirming the homogeneity and discipline in the students who physical activity would be used.
Keywords: Physical Education. Games. Scouts.